1996
DOI: 10.1002/(sici)1521-186x(1996)17:6<467::aid-bem6>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Weak extremely-low-frequency magnetic field-induced regeneration anomalies in the planarianDugesia tigrina

Abstract: We recently reported that cephalic regeneration in the planarian Dugesia tigrina was significantly delayed in populations exposed continuously to combined parallel DC and AC magnetic fields. This effect was consistent with hypotheses suggesting an underlying resonance phenomenon. We report here, in a parallel series of investigations on the same model system, that the incidence of regeneration anomalies presenting as tumor‐like protuberances also increases significantly (P < .001) in association with exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…It was found that combined MFs produced a stimulating effect on reproduction and regeneration of planarians [Novikov et al, ]. However, combined MFs also led to regeneration anomalies [Jenrow et al, ]. In our study, RMFs (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It was found that combined MFs produced a stimulating effect on reproduction and regeneration of planarians [Novikov et al, ]. However, combined MFs also led to regeneration anomalies [Jenrow et al, ]. In our study, RMFs (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Influence of MFs exposure on regeneration of planarians had been previously reported by Jenrow et al [] and Novikov et al []. In their studies, combined (weak static MF/alternating MF) collinear MFs were used for exposure.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a significantly higher rate of head regeneration was reported during exposure to a patterned electromagnetic field, resulting from the increasing number of biochemical pathways associated with cell proliferation, in particular, the p38-MAPK and hsp70 pathways [Tessaro and Persinger, 2013]. Furthermore, the weak ELF magnetic field was likely teratogenic in planarian head regeneration [Jenrow et al, 1996]. However, in this study, the results indicated that the high magnetic fields provided by the superconducting magnet had no lethal or teratogenic effect on planarian head regeneration, thus yielding the same conclusion that the strong static magnetic field was safe for living organisms [Yamaguchi-Sekino et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating this picture, possibly, is Faraday's Law of Induction. Increasing the intensity of B will always cause larger induced currents, possibly leading to extra biological responses that are independent of those that are q/m-related [Jenrow et al 1996].…”
Section: Ion Parametric Resonancementioning
confidence: 99%